Eksplorasi Peran Mediasi Pembelian Impulsif pada Pengaruh Persepsi Harga, Fear Of Missing Out (FOMO), dan Literasi Keuangan terhadap Pengelolaan Keuangan Generasi Z User Tiktok Shop - Nadya Febrianti Prayogi; Ariati Anomsari; Almira Santi Samasta; Suhita Whini Setyahuni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study explores the mediating role of impulsive buying on the influence of price perception, Fear Of Missing Out (FOMO), and financial literacy on the financial management of Gen Z TikTok Shop Users at Dian Nuswantoro University. With the results of a descriptive quantitative approach of 122 respondents, using non-probability sampling techniques specifically purposive sampling and snowball sampling, it was found that price perception and FOMO were proven to have a significant positive effect and thus play a strong role in increasing impulsive behavior. Conversely, financial literacy had a significant negative effect, low financial literacy encouraged unplanned spending to increase. Impulsive buying was proven to mediate the relationship between the influence of price perception, Fear Of Missing Out (FOMO), and financial literacy on individual financial management. The results of the study support the need for the reach of objects and variables related to the financial management of the younger generation on various digital platforms.